The bat fauna (Mammalia, Chiroptera) of Stary Zhaden Zakaznik, Southern Belarus - Dombrovski, V.; Fenchuk, V.; Zhurauliou, D. (Праці теріологічної школи, 2017)
The results of bat research conducted in Stary Zhaden Zakaznik (area 170 km2, 51.9 N 27.6 E, central part of the Pripyat Polesia region, Southern Belarus) during 2015–2016 con¬firmed the occurrence of 12 species of bats (listed in descending order of occurrence): Pipistrellus pygmaeus, Nyctalus noctula, Vespertilio murinus, Plecotus auritus, Barbastella barbastellus, Myotis brandtii, Nyctalus lasiopterus, Pipistrellus nathusii, Nyctalus leisleri, Myotis nattereri, Eptesicus nilssonii, Myotis daubentonii. The breeding of five bat species in this region, such as B. barbastellus, M. brandthii, M. nattereri, E. nilssonii, and N. lasiopterus, is confirmed for the first time. Research results show the high significance of the Pripyat Polesia region in conservation of bats and biological diversity on both national and European scales.